Dynamic load balancing in the PICADOR plasma simulation code - Bastrakov, S.I.; Meyerov, I.B.; Surmin, I.A.; Malyshev, A.S.; Shiryaev, M.A.; Efimenko, E.S.; Gonoskov, A.A. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2013)
The load balancing problem for the particle-in-cell plasma simulation on cluster systems is considered. A dynamic load balancing scheme based on the rectilinear partitioning is proposed. An efficient imbalance estimation and the implementation of repartitioning are discussed. Experimental data show that, for significantly imbalanced problems, our implementation is at least two times more efficient compared to the uniform partitioning. The load balancing overhead is less than 1% of the total computational time. This work was prepared in the UNN-Intel ITLab supported by the Federal Target Program «Scientific and educational staff of innovative Russia» (contract N 14.B37.21.0393) and by the Grant Council of the President of the Russian Federation (project code MX–1960.2012.9). The paper is recommended for publication by the Program Committee of the International Scientific Conference «Scientific Service in Internet: All Incarnations of Parallelism» (http://agora.guru.ru/abrau2013).